Shadow banking in the Euro area: an overview - Klára Bakk-Simon; Stefano Borgioli; Celestino Giron; Hannah Sabine Hempell; Angela Maddaloni; Fabio Recine; Simonetta Rosati (European Central Bank (ECB), 2012)
Shadow banking, as one of the main sources of financial stability concerns, is the subject of much international debate. In broad terms, shadow banking refers to activities related to credit intermediation and liquidity and maturity transformation that take place outside the regulated banking system. This paper presents a first investigation of the size and the structure of shadow banking within the euro area, using the statistical data sources available to the ECB/Eurosystem. Although overall shadow banking activity in the euro area is smaller than in the United States, it is significant, at least in some euro area countries. This is also broadly true for some of the components of shadow banking, particularly securitisation activity, money market funds and the repo markets. This paper also addresses the interconnection between the regulated and the non-bank-regulated segments of the financial sector. Over the recent past, this interconnection has increased, likely resulting in a higher risk of contagion across sectors and countries. Euro area banks now rely more on funding from the financial sector than in the past, in particular from other financial intermediaries (OFIs), which cover shadow banking entities, including securitisation vehicles. This source of funding is mainly shortterm and therefore more susceptible to runs and to the drying-up of liquidity. This finding confirms that macro-prudential authorities and supervisors should carefully monitor the growing interlinkages between the regulated banking sector and the shadow banking system. However, an in-depth assessment of the activities of shadow banking and of the interconnection with the regulated banking system would require further improvements in the availability of data and other sources of information.
Keywords: C22; E27; 330; Bank Regulation; repo markets; securitisation; Shadow banking; Finanzintermediation; Investmentbank; Finanzsektor; Geldpolitik; Geldpolitische Transmission; Systemrisiko; Wirkungsanalyse; Eurozone; EU-Staaten